Orthodontists of Nepal: The demographic and professional characteristics (Orthodontic Journal of Nepal, 2020)
Introduction: Orthodontists are specialist human resource in dentistry. They are essential for the treatment of malocclusion and correction of dentofacial anomalies. Human resource data is required for the planning and implementation of orthodontic service in the country. So the objective of this study was to assess the distribution of Nepali orthodontists according to demographic and professional characteristics.Materials and Method: The study was carried on Nepali orthodontists graduated till December 2020. Demographic details on age, gender, ethnicity, address and professional details on graduation year, university, country, working sector, working district were obtained from the records of Nepal Medical Council and Orthodontic & Dentofacial Orthopedic Association of Nepal, and from the personal communications. The collected data were entered in Microsoft Excel sheet, which was transferred to SPSS Version 20 program for category description.Result: A total of 164 qualified Nepali orthodontists were present as of December 2020. The mean age of the orthodontists was 37.65 (±7.047) years and male to female ratio was 6:4. Among all; 145 were working in Nepal and 80 (48.8%) were working in Kathmandu valley. Among the working orthodontists; 83.4% served in private and 16.6% served in public sector. Orthodontists serve in 24 districts of all seven provinces of Nepal.Conclusion: The number of Nepali orthodontists has increased remarkably after the year 2010. Majority of the orthodontists are working in private sector; those serving in public sector and academia also work extra time at private clinics. Very few orthodontists are present in Karnali and Sudurpaschim province.